Food choices and the transition to sustainable diets: motivations among Brazilian university students with different dietary profiles - Ramos, Fernanda dos Santos; Mello, Nathalia Soares Brum de; Oliveira, Letícia de (Sustainability in Debate, 2025)
In a context of growing demand for sustainable food systems, this study examines the psychosocial determinants of food choices among Brazilian university students, employing the Food Choice Questionnaire (FCQ) expanded to include a “concern for animals” dimension. The sample consisted of 1,582 students. Four dietary groups (omnivores, flexitarians, vegetarians, and vegans) were compared using ANOVA and Tukey’s post-hoc tests. The results indicated statistically significant differences across all evaluated dimensions. Health, convenience, and sensory appeal yielded the highest average scores. Vegetarians and vegans placed more value on ethical aspects and animal welfare. Animal concern emerged as the most salient dimension differentiating the groups, with progressively higher scores from omnivores to vegans. Omnivores placed less importance on ethics and animal welfare. The findings contribute to the understanding of food motivations in contexts of food transition and provide directions for promoting more sustainable choices among university students.